Evaluation of Warionia saharae Ethanolic Extracts under controlled conditions: Potent Acaricidal and Repellent Activities Against Tetranychus urticae Koch. (Acari: Tetranychidae) - Redouan Qessaoui; Salahddine Chafiki; Abdelmalk Mahroug; Abdelhadi Ajerrar; Rachid Elaini; Rachid Bouharroud (African and Mediterranean Agricultural Journal - Al Awamia)
Tetranychus urticae is a highly polyphagous species that infests a wide range of ornamental and vegetable crops, causing damage to the appearance of the crops and resulting in significant losses in yield. This study aimed to evaluate the acaricidal and repellent effects of the Warionia saharae extract on the adults of T. urticae. To achieve this objective, five concentrations of ethanol W. saharae extract (C1 (50%), C2 (25%), C3 (12,5%), C4 (6%), and C5 (1%)) were tested along with a control (distilled water) using a randomized complete block design with four replicates for each treatment. The results demonstrated a significant mortality rate in T. urticae adults for all five concentrations at 24, 48, and 72 h after treatment (p < 0.001). The highest mortality rates (86% to 100%) were observed for all concentrations 72 h after treatment. Moreover, concentrations C1 and C2 showed mortality rates exceeding 69% as early as 24 h after treatment. Furthermore, a repellency effect was observed for concentrations C1, C2, and C3 against T. urticae adults. Therefore, the results of this study demonstrate that W. saharae extract is an effective acaricide, exhibiting LC50 values of 37.99% and 41.89% at 48 and 72 h, respectively.